PERBANDINGAN EFEKTIVITAS OBAT GOLONGAN STATIN (SIMVASTATIN, ATORVASTATIN, DAN ROSUVASTATIN) SEBAGAI ANTIINFLAMASI SECARA IN VIVO - Ahmad Zaki Hafizi; Agung Biworo; Alfi Yasmina (Homeostasis, 2019)
Abstract:Statins indicated in patients with dyslipidemia are known to have aanti-inflammatory effect. The study was to compare the effectiveness of simvastatin, rosuvastatin, and atorvastatin as anti-inflammatory agent. This study using Rattus norvegicus from the Sprague-Dawley strain with induction of inflammation. 30 rats were classified into 5 groups. The efficacy of anti-inflammatory effect was assessed by measuring the volume of the hind paw oedema. The results showed that the average volume each group was as follows: aspirin -3.67 ml, placebo 21.60 ml, simvastatin 12.50 ml, atorvastatin 7.20ml, and rosuvastatin 3.40ml, which showed significantly different results between groups with the ANOVA and Tukey test (p <0.05), except between rosuvastatin and atorvastatin (p = 0.24). The largest antiinflammatory efficacywas indicated by aspirin, rosuvastatin, atorvastatin, simvastatin, and placebo, consecutively. It can be concluded that there are significant differences efficacy between statin  except between rosuvastatin and atorvastatin. Keywords: anti-inflammatory, simvastatin, atorvastatin, rosuvastatin. Abstrak: Statin yang diindikasikan pada pasien dislipidemia diketahui memiliki efek antiinflamasi. Penelitian ini bertujuan untuk membandingan efektivitas obat golongan statin, yaitu simvastatin, rosuvastatin, dan atorvastatin sebagai antiinflamasi. Penelitian menggunakan hewan coba Rattus norvegicus galur Sprague-Dawley dengan induksi inflamasi pada plantar kaki hewan coba. 30 ekor tikus dikelompokkan menjadi 5, yaitu kelompok simvastatin, rosuvastatin, atorvastatin, aspirin, dan plasebo. Efektivitas antiinflamasi dinilai dengan mengukur volume kaki. Hasil penelitian menunjukkan rerata selisih volume kaki pada masing-masing kelompok sebagai berikut: aspirin -3,67 ml, plasebo 21,60 ml, simvastatin 12,50 ml, atorvastatin 7,20 ml, dan rosuvastatin 3,40 ml, yang menunjukkan hasil berbeda bermakna antar kelompok dengan uji ANOVAdan uji Tukey (p < 0,05), kecuali antara kelompok rosuvastatin dan atorvastatin (p = 0,24). Efektifitas antiinflamasinya dari yang paling besar ditunjukkan oleh aspirin, rosuvastatin, atorvastatin, simvastatin, dan plasebo. Dapat disimpulkan bahwa terdapat perbedaan efektivitas yang bermakna antara obat statin sebagai antiinflamasikecuali antara rosuvastatin dan atorvastatin. Kata-kata kunci:anti inflamasi, simvastatin, atorvastatin, rosuvastatin